Spiritualitas Sunder Warumbe Dalam Puisi “Nyanyian Angsa” Karya W.S Rendra - Kristiawan, Purnomo (IAKN Ambon, 2023)
Prostitution or prostitution is one type of work that has existed for the rest of human history. Joshua 2:1, 6:17-25 tells us that a prostitute named Rahab was used by God to hide Israel's scouts from the Canaanites. In Luke 7:36-50 it is said that the Lord Jesus forgave a sinful woman (prostitute) who oiled His feet. This article seeks to examine the issue of prostitution is actually a structural problem related to economic, educational, justice, political and other issues. In the poem, The Song of the Swan, the responses of the Pimps, Doctors, and Priests to the Olive Mary are countered by the response of the